Use of effective dose. (June 2016) - Harrison, J.D.; Balonov, M.; Martin, C.J.; Ortiz Lopez, P.; Menzel, H-G.; Simmonds, J.R.; Smith-Bindman, R.; Wakeford, R.
International Commission on Radiological Protection (ICRP) Publication 103 provided a detailed explanation of the purpose and use of effective dose and equivalent dose to individual organs and tissues. Effective dose has proven to be a valuable and robust quantity for use in the implementation of protection principles. However, questions have arisen regarding practical applications, and a Task Group has been set up to consider issues of concern. This paper focusses on two key proposals developed by the Task Group that are under consideration by ICRP: (1) confusion will be avoided if equivalent dose is no longer used as a protection quantity, but regarded as an intermediate step in the calculation of effective dose. It would be more appropriate for limits for the avoidance of deterministic effects to the hands and feet, lens of the eye, and skin, to be set in terms of the quantity, absorbed dose (Gy) rather than equivalent dose (Sv). (2) Effective dose is in widespread use in medical practice as a measure of risk, thereby going beyond its intended purpose. While doses incurred at low levels of exposure may be measured or assessed with reasonable reliability, health effects have not been demonstrated reliably at such levels but are inferred. However, bearing in mind the uncertainties associated with risk projection to low doses or low dose rates, it may be considered reasonable to use effective dose as a rough indicator of possible risk, with the additional consideration of variation in risk with age, sex and population group.